Alterations in Cellular Iron Metabolism Provide More Therapeutic Opportunities for Cancer - Liangfu Zhou (International Journal of Molecular Sciences, 2018)
Iron is an essential element for the growth and proliferation of cells. Cellular iron uptake, storage, utilization and export are tightly regulated to maintain iron homeostasis. However, cellular iron metabolism pathways are disturbed in most cancer cells. To maintain rapid growth and proliferation, cancer cells acquire large amounts of iron by altering expression of iron metabolism- related proteins. In this paper, normal cellular iron metabolism and the alterations of iron metabolic pathways in cancer cells were summarized. Therapeutic strategies based on targeting the altered iron metabolism were also discussed and disrupting redox homeostasis by intracellular high levels of iron provides new insight for cancer therapy. Altered iron metabolism constitutes a promising therapeutic target for cancer therapy.